Death anxiety and its association with severity of mental illness in patients with depression and schizophrenia - Shahraki Mojahed, Hamidreza; Nakhaei, Somayeh (Universa Medicina, 2022)
BackgroundDeath and the anxiety of it becomes more apparent when confronted with a chronic disease. The aim of this study was to determine the level of death anxiety among patients with depression and schizophrenia, and the relationship between severity of the symptoms and death anxiety in these patients. MethodsA cross-sectional study was conducted on 29 patients with a depressive disorder, 18 with schizophrenia spectrum disorder and 31 healthy subjects, through face-to-face interviews. The general severity of the psychiatric disorder was measured using the Clinical Global Impression Scale (CGI). The severity of depressive symptoms was measured using the Beck Depression Inventory (BDI). Psychosocial performance was measured using the personal and social performance scale (PSP). To evaluate death anxiety, the Bochum Questionnaire on attitude to death and death anxiety 2.0 (BOFRETTA 2.0) was used. One-way ANOVA and Pearson correlation tests were used to analyze the data. ResultsRegarding the BOFRETTA attitude scale, the schizophrenic patients (23.1±9.12) showed significantly higher scores than healthy subjects (18.4 ±4.56) and depressive patients (19.8 ± 5.20) (p<0.050). The healthy controls achieved the least scores of BOFRETTA anxiety scale followed by depressive (30.67±10.33) and schizophrenic patients (31.30±12.18). However, there were no significant between-group differences regarding this scale. We found significant correlations of all BOFRETTA dimensions (attitude, anxiety, sum score) with CGI, PSP and BDI. ConclusionThere was a significant relationship between the severity of symptoms and death anxiety in both depressed and schizophrenic patients. However, the latter showed a more negative attitude towards death.